Framework to assess performance and impact of pluralistic agricultural extension systems: The best-fit framework revisited - Faure, Guy; Davis, Kristin E.; Ragasa, Catherine; Franzel, Steven; Babu, Suresh Chandra (International Food Policy Research Institute, 2016)
Extension and advisory services (EAS) are well recognized as a key factor in contributing to agricultural productivity and growth. However, rigorous evaluation of EAS approaches and assessment of complex national or subnational pluralistic EAS systems are rare. This working paper examines the literature on experiential and empirical insights and explores methods to assess complex pluralistic EAS systems. The authors present conceptual thinking on innovation systems and EAS, and review the IFPRI “best-fit” framework. This framework remains relevant because it is based on a holistic perspective with an impact pathway orientation. The paper aims to operationalize and improve the best-fit framework to guide the evaluation of complex EAS systems. The authors draw on and summarize existing literature to illustrate methods and tools used to analyze each component of the framework. The review pays close attention to the literature and methods for assessing the diversity of service providers and their various delivery tools and learning approaches. The discussion also pays close attention to the interaction of each component and how it affects the performance and impact of EAS from a systems perspective. This paper adds key points and considerations on how to operationalize the best-fit framework to carry out evaluations of pluralistic EAS.